Rearticulation of the Meaning of Jihad in the Post-Normal Era: A Hermeneutic Study from Hasan Hanafi's Perspective - Marjani, Muhammad Yusuf; Mukafi, Ahmad; Yusuf, Kamal (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The concept of jihad is one of the most frequently semantically reduced Islamic terms in contemporary discourse, particularly since the rise of the global war on terror narrative, which has often associated it with violence, extremism, and threats to global security. Historically and normatively, however, jihad encompasses a far broader spectrum of meanings, including spiritual, moral, intellectual, social, and communal defensive dimensions. This study aims to reconstruct the meaning of jihad through the hermeneutical perspective of Hassan Hanafi by tracing its historical transformations and rearticulating its relevance within the context of Post-Normal Times. This research employs a qualitative library-based approach within an interpretive-critical paradigm. The methodological framework integrates Hassan Hanafi’s transformational hermeneutics, Edmund Husserl’s phenomenology, conceptual genealogy, and Ziauddin Sardar’s Post-Normal Times framework. The analysis is conducted through three layers of consciousness: eidetic consciousness, which seeks to extract the universal essence of jihad through lexicographical analysis; historical consciousness, which traces the transformation of jihad’s reception across various horizons of Islamic civilization; and practical consciousness, which reconstructs jihad in response to contemporary challenges. The findings indicate that, in its eidetic sense, jihad refers to the conscious and maximal mobilization of all human capacities in confronting obstacles to achieve a meaningful objective. Historically, jihad evolved from a form of moral-spiritual resistance during the revelatory period into a juridical-political construct in the classical era, later becoming a language of anti-colonial liberation, before experiencing semantic crisis during the era of the global war on terror. In the context of Post-Normal Times, jihad must be rearticulated as a multidimensional concept of struggle encompassing epistemic, communicative-da‘wah, ethical-social, ecological, and spiritual dimensions as a response to the complexity, chaos, and uncertainty of the contemporary age.